Pengembangan Bahan Ajar E-Book Menggunakan Flip Builder untuk Meningkatkan Pemahaman Konsep pada Materi Bumi Berubah - Adisty Rizka Ramadini; Lufty Hari Susanto; Nur Hikmah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study addressed the low conceptual understanding of fifth-grade students at SDN Ciherang 3, Cianjur Regency, on the IPAS topic of Earth Changes. Although various digital teaching media have been developed for elementary science instruction, few have specifically been designed to overcome students' conceptual understanding difficulties through interactive, multimedia-based e-books. It aimed to develop, assess the feasibility of, and evaluate the effectiveness of a Flip Builder-based e-book in improving students’ conceptual understanding. Using the Research and Development (R&D) method with the ADDIE model, the study involved 27 fifth-grade students. Data were collected through observations, interviews, validation questionnaires, response questionnaires, and pre-test and post-test assessments. The results showed that the e-book was highly feasible, receiving validation scores of 98% from the media expert and 100% from the language and material experts. It was also highly practical, with positive responses from students (96.9%) and teachers (100%). Students’ average scores increased from 65.05 on the pre-test to 89.35 on the post-test, with an N-Gain score of 0.76, indicating high effectiveness. These findings demonstrate that the Flip Builder-based e-book is feasible, practical, and effective in enhancing students’ conceptual understanding of Earth Changes.